2002
DOI: 10.1176/appi.ajp.159.7.1165
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Altered Glutamate and GABA Metabolism in the Dorsolateral Prefrontal Cortex of Aged Schizophrenic Patients

Abstract: Greater phosphate-activated glutaminase and glutamic acid decarboxylase activities, specific to schizophrenia patients, provide additional biochemical evidence that dorsolateral prefrontal cortex glutamate and GABA metabolism is altered in schizophrenic subjects. These greater activities are consistent with models of a dysregulated glutamatergic/GABA-ergic state in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 56 publications
9
61
5
Order By: Relevance
“…Taken together, unchanged enzyme activity and expression changes of glutamine synthetase and GSLP in opposite directions suggest that these enzymes may be differentially regulated in disease states by astrocytes. Furthermore, these data suggest that the study of glutamine synthetase may be confounded by the presence of multiple distinct isoforms and that past reports of unchanged glutamine synthetase activity may have been due to a summation of activity from multiple isoforms (Gluck et al, 2002).…”
Section: Expression Of Glutamine Synthetase In Schizophreniamentioning
confidence: 87%
See 1 more Smart Citation
“…Taken together, unchanged enzyme activity and expression changes of glutamine synthetase and GSLP in opposite directions suggest that these enzymes may be differentially regulated in disease states by astrocytes. Furthermore, these data suggest that the study of glutamine synthetase may be confounded by the presence of multiple distinct isoforms and that past reports of unchanged glutamine synthetase activity may have been due to a summation of activity from multiple isoforms (Gluck et al, 2002).…”
Section: Expression Of Glutamine Synthetase In Schizophreniamentioning
confidence: 87%
“…In turn, this could cause astrocytes to decrease production of glutamine synthetase or to increase protein disassembly and degradation to correct for abnormally high activity (Kosenko et al, 2003). So far, studies have not shown changes to glutamine synthetase activity in the brain in schizophrenia (Burbaeva et al, 2003, Gluck et al, 2002.…”
Section: Expression Of Glutamine Synthetase In Schizophreniamentioning
confidence: 99%
“…Decreased neuropil and neuronal size, rather than neuronal loss have been observed in the hippocampus (Benes et al, 1991). Altered functioning of neurotransmitters might be taking place (Deakin & Simpson, 1997b;Gluck et al, 2002). As reviewed by Deakin and Simpson (1997a), there is an asymmetric loss of glutamate terminals in the temporal lobe and reduced GABA function secondary to a loss of glutamatergic input.…”
Section: Discussionmentioning
confidence: 99%
“…An antagonism at this location could, in turn, cause regional hypermetabolism from increased glutamate release (Gluck et al, 2002;Theberge et al, 2002;Bartha et al, 1997;Moghaddam et al, 1997;Moghaddam and Adams, 1998). The mechanism for this phenomenon may be attributed to disinhibition of inhibitory interneurons in the anterior thalamus, basal forebrain, or frontal cortex (Farber, 2003;Carter et al, 2004;Tomitaka et al, 2000).…”
Section: Introductionmentioning
confidence: 99%